Constructing Fixed-Point Combinators Using Application Survival - Goldberg, Mayer (BRICS Report Series, 1995)
The theory of application survival was developed in our Ph.D. thesis as an approach for reasoning about application in general and self-application in particular. In this paper, we show how application survival provides a uniform framework not only for for reasoning about fixed-points, fixed-point combinators, but also for deriving and comparing known and new fixed-point combinators.